2018
DOI: 10.5888/pcd15.170247
|View full text |Cite
|
Sign up to set email alerts
|

Television Viewing Time, Physical Activity, and Mortality Among African Americans

Abstract: BackgroundProlonged television viewing time, a marker of sedentary activity, is independently associated with increased all-cause mortality; however, this association has rarely been studied in African Americans. The objective of our study was to examine the association between television viewing time and mortality among African Americans by using data from the Jackson Heart Study (JHS).MethodsWe studied 5,289 participants from the JHS study who reported television viewing time (h/day) in the JHS baseline ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Diaz and colleagues reported that the positive associations of sedentary time and bout duration with all-cause mortality did not vary by age, sex, race, BMI or moderate-to-vigorous physical activity (27). Further, Imran et al reported that in African Americans the results were similar when they excluded those with high and low BMI, those with low leisure physical activity, and those without a high school diploma (24). Theou and colleagues reported a significant association between accelerometer-derived sedentary time and all-cause mortality in NHANES; the association was statistically significant in physically inactive adults but not in physically active adults (31).…”
Section: Mortality Outcomesmentioning
confidence: 98%
See 3 more Smart Citations
“…Diaz and colleagues reported that the positive associations of sedentary time and bout duration with all-cause mortality did not vary by age, sex, race, BMI or moderate-to-vigorous physical activity (27). Further, Imran et al reported that in African Americans the results were similar when they excluded those with high and low BMI, those with low leisure physical activity, and those without a high school diploma (24). Theou and colleagues reported a significant association between accelerometer-derived sedentary time and all-cause mortality in NHANES; the association was statistically significant in physically inactive adults but not in physically active adults (31).…”
Section: Mortality Outcomesmentioning
confidence: 98%
“…All studies used prospective cohort designs, with follow-up periods ranging from 2.3 to 19.4 years. The sedentary exposures varied across studies: five studies used self-reported sitting time (17)(18)(19)(20)(21), seven studies used self-reported TV viewing time (17,18,(22)(23)(24)(25)(26), and five studies used accelerometer-derived estimates of sedentary time (27)(28)(29)(30)(31). All studies included an estimate of duration of sedentary behavior (sedentary time) as an exposure, while three studies also included a marker of bouts or breaks in sedentary time as an exposure (27)(28)(29).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study analyzing the mortality rates of people with >10 hours and <5 hours of sitting times a day, the sitting time was significantly correlated with all-cause mortality (odds ratio [OR], 1.16; 95% CI, 1.04– 1.29; P<0.05) [ 25 ]. In a study that examined the correlation between the television viewing time and all-cause mortality, the people who watched television for ≥6 hours a day had a two-fold higher all-cause mortality risk compared to the people who watched television for <2 hours a day (hazard ratio [HR], 1.98; 95% CI, 1.25–3.15) [ 26 ] whereas the people who watched television for ≥4 hours a day had a 1.5 times higher all-cause mortality risk compared to the people who watched TV for <2 hours a day (HR, 1.48; 95% CI, 1.19–1.83) [ 27 ].…”
Section: Sedentary Lifestyles and Health Risksmentioning
confidence: 99%